Tactile Sensing Technologies in Robotics: A Review of Sensors, Materials, and Applications - Sai Preetham Anumasu (International Journal of Robotics and Automation in Mechanics, 2025)
Tactile sensing, which closely resembles the human sense of touch, is an essential capability in modern robotics. It enables robots to detect and interpret physical interactions with objects, surfaces, and living beings, thereby allowing them to operate more intelligently and adaptively in complex environments. Unlike visual or auditory sensors, tactile sensors provide direct feedback about contact, pressure, texture, force, temperature, and even vibration. These sensory cues are vital for improving the dexterity, safety, and precision of robotic systems, especially in tasks involving manipulation, exploration, and physical interaction. In recent years, there has been significant progress in the field of tactile sensing, driven by innovations in materials science, nanotechnology, and flexible electronics. Developments in artificial skin, soft and stretchable materials, and sensor miniaturization have opened up new possibilities for integrating tactile sensors into robotic hands, grippers, limbs, and even full-body robotic platforms. These advancements have made tactile sensing more reliable, compact, and energy- efficient, making it feasible to deploy in both industrial and service-oriented robotics. This review article provides a comprehensive overview of the current landscape of tactile sensing technologies. It focuses on various sensor types—such as capacitive, piezoresistive, piezoelectric, optical, and magnetic sensors—and evaluates their principles of operation, benefits, and limitations. In addition, the review explores a wide range of materials used in sensor design, from conventional polymers and conductive composites to emerging smart materials like hydrogels and piezoelectric polymers.
Keywords: Tactile sensors; artificial skin; capacitive sensing; flexible electronics; human-robot interaction; piezoresistive materials; robotic manipulation